EKSPEKTASI DAN PERSEPSI WISATAWAN TERHADAP MAKANAN TRADISIONAL DI BADUNG SELATAN – BALI - Ni Luh Kartini; Sri Wahyuningsih (Jurnal Ilmiah Hospitality, 2022)
Every region in Indonesia has a special food that has the potential to be developed as a tourist attraction. So far, the study of traditional food is still common sense and limited to food characteristics and marketing strategies. This article discuss the quality of traditional food in terms of tourists regarding the quality of the food itself from the analysis of expectations and perceptions of tourists towards the quality of traditional Balinese food at the restaurant at Pak Malen's Warung Babi Guling, Pak Dobiel's Warung Babi Guling and Gilimanuk Chicken Warung. The focus of the article is to discuss differences in the characteristics of tourists, understand differences in expectations and perceptions of tourists using Gap Analysis and proposed improvements to improve food quality. The results of this study represent the difference between perceptions and expectations and it is also recognized that aroma, cleanliness and price factors are considered important by consumers. Looking at the results of the study, it was proposed improvements to improve food quality with the use of seasoning standards, improve cleanliness and use of menus.